Islamic Religious Education in the Sultanate of Siak Sri Indrapura (1917-1945): A Social History - Khairiah, Siti; Alyusufi, Abdulhaleem Obaid A.; Alkahtani, Hezam Sultan (JURNAL INDO-ISLAMIKA, 2024)
Condition of society in the Sultanate of Siak Sri Indrapura moment entering the 20th century experienced instability due to the Dutch government continued to disturb the Siak Sultanate. Meanwhile, Sultan Sjarif Kasim II only served as a traditional and religious leader because he no longer had autonomous rights. Through religion, Sulthan Sjarif Kasim II made education the main focus of educating society. With the Sultan's persistent efforts, Islamic religious education was implemented, which started traditionally, then continued through institutions, namely Madrasah Taufiq Alhasjimiah Madrasah (1917) for men only and Madrassatoen Nisa' (1933) for women only. This article has revealed the influence of Islamic religious education in the Sultanate of Siak Sri Indrapura on the people of Riau Province today.